I wish you more - Rosenthal, Amy Krouse; Lichtenheld, Tom (San Francisco : Chronicle Books, 2015)
In simple text and pictures, the author and illustrator create a compendium of small daily moments.
AD 360
Keywords: Wishes -- Juvenile fiction; English language -- Comparison -- Juvenile fiction